2023
DOI: 10.18632/aging.204581
|View full text |Cite
|
Sign up to set email alerts
|

ANGPTL2 promotes VEGF-A synthesis in human lung cancer and facilitates lymphangiogenesis

Abstract: Lung cancer is an extremely common cancer and metastatic lung cancer has a greatly low survival rate. Lymphangiogenesis is essential for the development and metastasis of lung cancer. The adipokine angiopoietin-like protein 2 (ANGPTL2) regulates tumor progression and metastasis, although the functions of ANGPTL2 in lung cancer are unknown. Analysis of data from TCGA genomics program, the GEPIA web server and the Oncomine database revealed that higher levels of ANGPTL2 expression were correlated with progressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…LYM index was developed based on LYM-related genes. LYM is closely associated with LUAD progression and metastasis ( 47 ), and based on the role of LYM in LUAD, we concluded that metastasis, invasiveness, and malignancy were higher in the LUAD patients in the high LYM index group compared to the low LYM index group. We confirmed that the prognosis of LUAD patients with a low LYM index was better than that of patients with a high LYM index, suggesting that LYM was an independent risk factor for LUAD, which is consistent with the findings of previous studies ( 48 50 ).…”
Section: Discussionmentioning
confidence: 92%
“…LYM index was developed based on LYM-related genes. LYM is closely associated with LUAD progression and metastasis ( 47 ), and based on the role of LYM in LUAD, we concluded that metastasis, invasiveness, and malignancy were higher in the LUAD patients in the high LYM index group compared to the low LYM index group. We confirmed that the prognosis of LUAD patients with a low LYM index was better than that of patients with a high LYM index, suggesting that LYM was an independent risk factor for LUAD, which is consistent with the findings of previous studies ( 48 50 ).…”
Section: Discussionmentioning
confidence: 92%
“…Precooled Matrigel was added to a 96-well plate and subjected to incubation at 37 °C for 30 min. HUVECs (2 × 10 4 cells/well) were suspended in 200 µL of conditioned medium and subsequently transferred to the corresponding well and incubated with supernatants from specified KTC-1 and BCPAP cells in 5% CO 2 at 37 °C for 8–12 h [ 28 ]. The images of tube structures were detected under an inverted bright-field microscope at 100× magnification, and photographs were taken.…”
Section: Methodsmentioning
confidence: 99%
“… 302 305 On one hand, VEGFA could function on VEGFR1/2 expressed by LECs and promote lymphanigongenesis. 304 , 305 On the other hand, VEGFA could indirectly induce lymphangiogenesis via recruitment of VEGFR1 + bone marrow-derived macrophages which in turn release both hemangiogenic and lymphangiogenic growth factors. 302 , 303
Fig.
…”
Section: Therapeutic Interventions and Clinical Research Progress Of ...mentioning
confidence: 99%